Healthcare Providers' Perceptions of Challenges with Frequent Users of Emergency Department Care in Switzerland: A Qualitative Study. (July 2021) - Bodenmann, Patrick; Kasztura, Miriam; Graells, Madison; Schmutz, Elodie; Chastonay, Oriane; Canepa-Allen, Marina; Moullin, Joanna; von Allmen, Michael; Lemoine, Melissa; Hugli, Olivier; Daeppen, Jean-Bernard; Grazioli, Véronique S.
Frequent users of emergency departments (FUED; ≥ 5 ED visits/year) commonly cumulate medical, social, and substance use problems requiring complex and sustained care coordination often unavailable in ED. This study aimed to explore ED healthcare providers' challenges related to FUED care to gain insight into the support and resources required to address FUED complex needs. An online survey was sent to all general adult emergency services within Switzerland (N = 106). Participants were asked to indicate the extent to which they perceived that FUED represented a problem and to describe the main challenges encountered. In total, 208 physicians and nurses from 75 EDs (70.7%) completed the survey. Among the 208 participants, 134 (64%) reported that FUED represented a challenge and 133 described 1 to 5 challenges encountered. A conventional content analysis yielded 4 main categories of perceived challenges. Negative consequences in the ED secondary to FUED's presence (eg, ED overcrowding, staff helplessness, and fatigue) was the most frequently reported challenge, followed by challenges related to FUEDs' characteristics (eg, mental health and social problems) leading to healthcare complexity. The third most frequently encountered challenge was related to the ED inappropriateness and inefficiency to address FUEDs' needs. Finally, challenges related to the lack of FUED healthcare network were the least often mentioned. ED healthcare providers experience a wide range of challenges related to FUED care. These findings suggest that currently EDs nor their staff are equipped to address FUEDs' complex needs.